Improving Access to Affordable Medicines: Looking at Prevailing Prices and Distribution of Village Drugstores in the Philippines - Aubrey D. Tabuga; Celia M. Reyes; Ronina D. Asis; Maria Blesila G. Datu (Philippine Institute for Development Studies (PIDS), 2011)
Drugs and medicines account for about half of the total medical out-of-pocket expenses of households. This share of drugs to total medical expenses is much higher for the poor than the rich. Thus, affordability of medicines is an important issue in poverty reduction. Recent efforts to improve affordability of medicines in the country were geared toward price mediation, advocacy campaigns for quality generic drugs, and creation of village drugstores (that is, the Botika ng Bayan and Botika ng Barangay), among others. This report shows how some of these efforts have gone as far as lowering the prices is concerned. It likewise examines the extent of establishment of DOH-initiated village drugstores in the effort to improve physical access to essential medicines. The goal is to identify areas with low access to affordable medicines by mapping out the geographic distribution of village drugstores.
Keywords: 330; Philippines; financial crisis; poverty impacts; school-level test scores; affordable medicines; Botika ng Barangay; Botika ng Bayan; Arzneimittel; Gesundheitsversorgung; Generika; Gesundheitskosten; Entwicklungsprojekt; Philippinen